Inhibition of Anti-Reflection Film Cracks on Plastic Substrates Using Nanolaminate Layer Deposition in Plasma-Enhanced Atomic Layer Deposition - Wang, Chi-Chieh; Wang, Cheng-Fu; Li, Meng-Chi; Su, Li-Chen; Kuo, Chien-Cheng (Technologies (Basel), 2025)
In this research, we mainly increase the adhesion of PMMA substrate and film, which is reflected in the environmental test. This study used plasma-enhanced atomic layer deposition (PEALD) to find the relationship between the intensity of XRD reflection peak and the root-mean-square surface roughness (σRMS) of hafnium dioxide (HfO2) at different thicknesses by reducing the plasma power at different process temperatures. In this experiment, HfO2 was found to have the highest intensity of XRD at its maximum thickness. According to the different intensities of XRD of HfO2 at different thicknesses, aluminum oxide (Al2O3) was inserted as crystallization cutoff layers, and the two materials were combined into nanolaminates. The corresponding σRMS value also changed from 1.25 to 0.434 nm after treatment under the fourth experimental design. This study improved this mismatch between interfaces by adjusting the yield strength and ductility using Al2O3 layers and by creating an inhibition layer. In addition, through the processing of inserted Al2O3 layers, the degree of crystallization was changed so that the material and substrate could maintain their normal surfaces without cracking after the environmental tests. After inserting five 1 nm thick Al2O3 layers, the environmental test results were improved. The test time was increased from the original 56 h to 352 h.